Patients from care homes who attend the emergency department: could they be managed differently. Issue 4 (23rd March 2009) - Carter, L; Skinner, J; Robinson, S
Abstract : Aims: To describe the demographics of patients from care homes who attend the emergency department (ED) and to estimate whether appropriate alternative care pathways could have been delivered to this patient group. Methods: A prospective descriptive study that gathered data on consecutive patients who presented to the ED of the Royal Infirmary of Edinburgh from adult care homes over a one-month period. A proforma was used to record details such as diagnosis, communication from the care home, referral details, patient transport and resuscitation status. Three general practitioners (GPs) assessed whether the patients could have been managed appropriately outwith the ED. Results: 114 patients were recruited over the month of the study. Seven patients were missed. Results showed that 40 care home patients (35%) came to the ED without an accompanying letter. 99 patients (87%) were brought to the department by ambulance. 58 patients (51%) who came to the ED from care homes were discharged, and of these 41 (71%) were transported back to the care home by non-ambulance transport. Three patients (3%) had a resuscitation status documented. GP review of case notes suggested that between nine (8%) and 46 (40%) could have been managed appropriately outwith the ED. Conclusion: In this study between 8% and 40% of patients could have been cared for outwith the ED. The findings highlight the importance of the provision of appropriate healthcare to care home residents and the current deficits that exist.